Sexing Bones: Improving Transparency of Sex Reporting to Address Bias Within Preclinical Studies. (13th November 2022) - Sharma, Aikta; Michels, Lysanne V; Pitsillides, Andrew A; Greeves, Julie; Plotkin, Lillian I; Cardo, Valentina; Sims, Natalie A; Clarkin, Claire E
ABSTRACT: Despite knowledge that sexually dimorphic mechanisms regulate bone homeostasis, sex often remains unreported and unconsidered in preclinical experimental design. Failure to report sex could lead to inappropriate generalizations of research findings and less effective translation into clinical practice. Preclinical sex bias (preferential selection of one sex) is present across other fields, including neuroscience and immunology, but remains uninvestigated in skeletal research. For context, we first summarized key literature describing sexually dimorphic bone phenotypes in mice. We then investigated sex reporting practices in skeletal research, specifically how customary it is for murine sex to be included in journal article titles or abstracts and then determined whether any bias in sex reporting exists. Because sex hormones are important regulators of bone health (gonadectomy procedures, ie, ovariectomy [OVX] and orchidectomy [ORX], are common yet typically not reported with sex), we incorporated reporting of OVX and ORX terms, representing female and male mice, respectively, into our investigations around sex bias. Between 1999 and 2020, inclusion of sex in titles or abstracts was low in murine skeletal studies (2.6%–4.06%). Reporting of OVX and ORX terms was low (1.44%–2.64%) and reporting of OVX and ORX with sex uncommon (0.4%–0.3%). When studies were combined to include both sexes and OVX (representing female) and ORX terms (representing male), a bias toward reporting of female mice was evident. However, when the terms OVX and ORX were removed, a bias toward the use of male mice was identified. Thus, studies focusing on sex hormones are biased toward female reporting with all other studies biased in reporting of male mice. We now call upon journal editors to introduce consistent guidance for transparent and accessible reporting of murine sex in skeletal research to better monitor preclinical sex bias, to diversify development of treatments for bone health, and to enable global skeletal health equity. © 2022 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).